Actions Against The Law Caused on The Action of Cancellation of The Grants : Study of Decision No. 156/Pdt.G/2017/PN. Tjk - Andika Pramudita; R. Ismala Dewi (Magister Ilmu Hukum Fakultas Hukum Universitas Syiah Kuala, 2021)
A grant is a free agreement in the form of giving part of the property to another person which cannot be withdrawn. Irrevocability is not an absolute provision because Article 1688 of the Civil Code regulates the conditions for withdrawing grants. However, the fact is that the withdrawal of the grant was given without heeding the provisions of the article. As a result, the withdrawal of grants that does not heed Article 1688 of the Civil Code will result in losses for the grantee and fall into the category of unlawful acts. The purpose of this study was to examine the cancellation of the grant granted by the judge in the decision no. 156/Pdt.G/2017/PN.Tjk with the Civil Code and analyze unlawful acts originating from the cancellation of grants that harm the grantee. To achieve this goal, the author uses a juridical-normative research method based on secondary data. Based on the research results the authors conclude that the cancellation of the grant in decision no. 156/Pdt.G/2017/PN.Tjk did not heed the provisions of Article 1688 of the Civil Code and as a result of the cancellation of the grant which harmed the grantee as compensation for fulfilling elements of an unlawful act in Article 1365 of the Civil Code.